Implementasi Program Dana Desa untuk Bantuan Peternakan di Desa Afoan Kecamatan Amfoang Utara Kabupaten Kupang - Yosina Akulas; Petrus Kase; I Putu Yoga B. Pradana (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the implementation of the Village Fund program through pig livestock assistance in improving the welfare of the community in Afoan Village, Kupang Regency. The approach used is descriptive qualitative with purposive sampling techniques, involving 15 informants consisting of village officials and beneficiary families. Data collection techniques were conducted through observation, interviews, and documentation, then analyzed using Miles and Huberman’s interactive model. The results show that the implementation of the program has not been optimal. Although communication and community participation have been running well, there are still several obstacles such as uneven distribution of assistance, weak monitoring systems, the lack of a clear timeline for fund disbursement, and technical issues such as livestock deaths reaching around 5%. The success rate of the program is estimated to be around 66%, while 33% is still in the development process. Economically, the program has not had a maximum impact on community welfare, but socially and politically, the program has gained strong support. Therefore, to improve the effectiveness of the program, improvements are needed in supervision, resource management, and the establishment of clearer regulations so that the program’s objectives can be achieved optimally and evenly.